Study on Utilization Pattern of Anti Dementia Drugs and Cost-Effective Analysis in India - Ray, S. (Current Aspects in Pharmaceutical Research and Development Vol. 2, 2021)
Background: The population suffering from Alzheimer’s disease (AD) and other dementias is estimated to increase every year in India, the reason being steady growth in the older population and stable increment in life expectancy. Aim: To evaluate the trend of clinical practices in India as well as cost analysis of anti dementia drugs in an Indian scenario. Material and Methods: Utilization pattern of anti dementia drugs studies was studied using literature survey and data mining of Prospective and Retrospective studies. Cost analysis was performed to evaluate wide variation in the prices of same anti dementia drug with different formulation in India. Results: Alzheimer’s disease is the most common subtype of dementia and Donepezil remains to be the most commonly prescribed drugs as indicated by Prospective and retrospective studies. Cost analysis of anti dementia drugs being manufactured by many companies across the different brands in India showed a very high variation in the minimum and maximum price. Cost ratio was highest for rivastigmine (1.5 mg capsule) and lowest for piracetam (400 mg tablet). It was observed that % cost variation of all the anti dementia drugs was above 100. Conclusion: Thus, in India, a wide variation in the prices of same drug with different formulation has a severe economic impact. More effort is needed to understand and analyze in terms of prescription, utilization pattern of anti dementia drugs as it has huge socioeconomic impact on patients and caregivers of mainly developing countries like India.